2018
DOI: 10.1002/cncr.31339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the posttransplant lymphoproliferative disorder subtype on survival

Abstract: The histologic subtype represents an important prognostic factor in PTLD, with patients with T-cell neoplasms exhibiting very poor OS. Possibly lower survival for certain subsets of patients with B-cell PTLD should be explored further and suggests the need for subtype-specific therapies to improve outcomes. Cancer 2018;124:2327-36. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Finally, patient survival can be very different in different organ transplants with different locations or WHO types of PTLD. We have accounted for WHO type; T cell PTLD remained independently significant in multivariate models, consistent with other recent reports . Certain individual locations were associated with higher risk of patient death in univariate analyses in our study, but each was present in very few subjects.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, patient survival can be very different in different organ transplants with different locations or WHO types of PTLD. We have accounted for WHO type; T cell PTLD remained independently significant in multivariate models, consistent with other recent reports . Certain individual locations were associated with higher risk of patient death in univariate analyses in our study, but each was present in very few subjects.…”
Section: Discussionsupporting
confidence: 90%
“…In our case series there was no difference in overall survival between CD30þ and CD30-PTLDs overall. We and others have previously shown that T-cell PTLD have a particularly poor prognosis [5,26,27]. In this case series, none of the 12 patients with T-cell PTLD survived a year.…”
Section: Discussionmentioning
confidence: 50%
“…Naturally the distribution of PTLD subtypes in the groups may affect survival. T-cell PTLDs, which have a particularly poor prognosis [2,20], were more common in the no ATG group and this may in part explain the inferior survival in this group. We also found that the non-germinal center type of DLBCL was more common in the ATG group compared with the no ATG group.…”
Section: Discussionmentioning
confidence: 95%
“…Survival in PTLD has improved in recent years due to an increased awareness of the diagnosis, the introduction of rituximab as PTLD treatment, and sequential treatment with rituximab followed by chemotherapy [13]. Older age, poor performance status, the presence of B symptoms (fever, night sweats, and weight loss), elevated serum lactate dehydrogenase (S-LDH), advanced stage, higher International Prognostic Index (IPI) score, extranodal disease, central nervous system (CNS) involvement, bone marrow involvement, monomorphic PTLD (and especially T-cell phenotype), hypoalbuminemia, elevated serum creatinine level (for kidney transplantation), type of transplant (thoracic organ), and hepatitis C infection have been reported as independent prognostic factors for inferior survival in various case series [2,5,[14][15][16][17][18][19][20]. Immunosuppressive regimens have seldom been included in these analyses of prognostic factors.…”
Section: Introductionmentioning
confidence: 99%